PESANTREN TRADISIONAL; AKAR PENYEBARAN ISLAM DAN BAHASA ARAB DI INDONESIA - Fauzi, Moch. Sony (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2007)
Traditional “pesantren” is the oldest education institution in Indonesia, in which student or santri studies many important materials in Islamic studies such as : Tauhid, Fiqh, and Tasawwuf. Arabic language as the language of the two main references in Islam, Quran and Hadith, and other classical reference in Islam is also the main object of study in Pesantren because of its importance as a means for understanding the references. The Arabic language is studied deeply especially in the aspect of grammar (qawaid). For this reason, pesantren is not only the center of Islamic studies but also the root of Arabic language in Indonesia.